1992
DOI: 10.1346/ccmn.1992.0400412
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Cation Distribution in Dioctahedral 2:1 Layer Silicates Using IR-Data: Application to Mössbauer Spectroscopy of a Glauconite Sample

Abstract: Abstraet--A new approach is described to computer simulate cation distribution in octahedral sheets of dioctahedral 2:1 layer silicates with vacant trans-octahedra. This approach makes use of the information on cation distribution at the one-dimensional level provided by integrated IR optical densities for the region of OH-stretching frequencies. By using this program it is possible to show that (1) the Mrssbauer spectrum of glauconite B. Patom conforms to the structural model composed of celandonite-like and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…The cation distribution with the minimum values for N22 and/or NFA corresponding to the number of R2+-R 2+ and Fe3+-A1 pairs, respectively, is accomplished by a penalty function, f(~) = ~/FA + (1-~)N22, where the at parameter is to be pre-set. Dainyak et al (1992) showed that three values of a have a practical meaning: if ~ is zero, pairs RZ+-R2+ should be forbidden in bl or b2 directions, at = 1 implies prohibition of Fe3+-A1 pairs in these directions, and both limitations take place at ~ = 0.5. …”
Section: Ir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…The cation distribution with the minimum values for N22 and/or NFA corresponding to the number of R2+-R 2+ and Fe3+-A1 pairs, respectively, is accomplished by a penalty function, f(~) = ~/FA + (1-~)N22, where the at parameter is to be pre-set. Dainyak et al (1992) showed that three values of a have a practical meaning: if ~ is zero, pairs RZ+-R2+ should be forbidden in bl or b2 directions, at = 1 implies prohibition of Fe3+-A1 pairs in these directions, and both limitations take place at ~ = 0.5. …”
Section: Ir Spectroscopymentioning
confidence: 99%
“…Dainyak et al (1992) elaborated a computer program in order to distribute four types of cations: Mg, Fe z+, Fe 3+ and A1 within a transvacant octahedral sheet. As basic global parameters of the octahedral cation distribution, the occurrence probabilities Wii (i, j = Mg, Fe z+, Fe 3+, AI) for cations of the i and j types bonded to OH groups were used.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Also, they found a tendency of Al and Fe to segregate from each other. Dainyak, Drits, and Heifits (1992) performed Mö ssbauer analysis on a transvacant glauconite and found that it presented celadonite-and illite-like domains in its octahedral sheet and that the crystallographic ''right'' and ''left'' cis-positions in a fixed b direction were not equally occupied by divalent and trivalent cations. Goodman, Nadeau, and Chadwick (1988) studied smectites from bentonites by means of Mö ssbauer and electron paramagnetic resonance spectroscopies and found that Fe was located in two different crystal field environments, which could be interpreted as either two phases, two crystallographic sites, or two different nearest neighbor compositions.…”
Section: Introductionmentioning
confidence: 99%
“…There is no problem in considering the presence of those domains in the octahedral sheet in a polar layer. The presence of domains in the octahedral sheet of2:1 phyllosilicates has already been reported (Dainyak et al 1992;Grauby et al 1993Grauby et al , 1994. It is likely that the higher charge in an illitic tetrahedral sheet, or the charge distribution, forces the transformation of the octahedral sheet.…”
Section: Discussionmentioning
confidence: 71%